IHDAD WANITA KARIR PERSPEKTIF HUKUM ISLAM - Singgih Mualim; Masruri Masruri (Fakultas Syariah, Prodi Ahwal As Syakhsiyah (AS) Universitas Nahdlatul Ulama Al-Ghazali (UNUGHA) Cilacap, 2023)
The discussion in this research reveals everything related to women in their activities outside the household, where women also have religious regulations that require and limit them in their activities when their husband dies, namely during the period of mourning or ihdad during the 'iddah period, namely 4 months and 10 days. This research explains the views of Islamic law, especially the Shafi'i school of thought, in responding to career women during bereavement. This research uses a library research method. Based on the research results, it was found that for a career woman, even though religious rules do not allow her to leave the house for 4 months and 10 days, for urgent reasons, namely regarding the needs of herself and her family, she is worried that the situation will disturb her faith, so leaving the house for activities is permissible by paying attention to religious rules.